2023
DOI: 10.1590/1519-6984.245197
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring pond water quality to improve the production of Labeo rohita (Hamilton, 1822) in Bannu Fish Hatchery of Bannu district, Khyber Pakhtunkhwa province; An Implications for artificial fish culture

Abstract: The water quality parameters of a fish pond are essential to be managing properly under control for successful operations of fish culture. Improper management of pond water quality during the juvenile stages can create stressful conditions to produce various harmful diseases, which may decrease the fish quality and results in low profits. The present study was aimed to monitored important water quality parameters of nursery ponds of Labeo rohita culturing in Bannu fish hatchery. The study duration was 75 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the present study, all the physico-chemical parameters explored were in consonance with the optimum range for survival and growth of fish 13,15 , except few parameters including dissolved oxygen, alkalinity, conductivity, hardness and calcium. This observation corroborates the previous report by Mustapha et al 16 , who investigate the the water supply system from Maiduguri water treatment plant.…”
Section: Physico-chemical Parameterssupporting
confidence: 74%
“…In the present study, all the physico-chemical parameters explored were in consonance with the optimum range for survival and growth of fish 13,15 , except few parameters including dissolved oxygen, alkalinity, conductivity, hardness and calcium. This observation corroborates the previous report by Mustapha et al 16 , who investigate the the water supply system from Maiduguri water treatment plant.…”
Section: Physico-chemical Parameterssupporting
confidence: 74%
“…As for the groups exposed to the toxic agent, there was only a slight variation in the pH, where an average of pH 8.1±05 was observed, remaining the other measures similar to the control group. Water conductivity and ammonia levels remained within standard values (below 500 µS/cm and 0.05 mg/L, respectively) (Masood et al, 2022).…”
Section: Resultsmentioning
confidence: 76%
“…The water parameters observed in all groups, including the control group, during both tests, were considered within the comfort level for tropical species, which has an optimal pH range between 6 and 8, dissolved oxygen (DO) greater than 5 and less than 9, and temperatures between 20 and 28 °C (Masood et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…TDS values were lower higher than those obtained by Njieassam [36] working on evaluating water quality of catfish tank aquaculture. However, these values were low and optimal for fish productivity [56] and were below the applicable range of 400 to 500 mg/L suitable for fish pond water sample [57]. The status of TDS (regression analysis) for all the studied holding tanks revealed that it had a positive and negative effect on survival and weight respectively.…”
Section: Discussionmentioning
confidence: 99%